The Incidence, Risk Factors and Characteristics of Late (>2 Years) Recurrence of Deep Venous Thrombosis - Bo Wu MD; Jian Fu MD; Haiyang Wang MD; Haiyan Yan MD; Jianming Sun MD; Haoyuan Wang MD; Lili Zhang MD (Clinical and Applied Thrombosis/Hemostasis)
Objective Recurrent deep venous thrombosis (RDVT) is a relatively frequent phenomenon; however, scarce literature is available on late RDVT (>2 years). This study aimed to investigate the incidence, associated risk factors, and characteristics of late RDVT. Methods We conducted a retrospective analysis of patients diagnosed with symptomatic lower extremity deep venous thrombosis (DVT) between April 2017 and April 2022. The incidence and mortality rates of late RDVT, as well as the demographic data, risk factors, and characteristics, were assessed. Additionally, a comprehensive Cox regression analysis was performed to evaluate 14 potential risk factors. Results Of the 638 patients with DVT, 89 (13.9%) experienced recurrence during a mean follow-up period of 30.10 ± 15.23 months. The RDVT group comprised 50 males and 39 females (the male-to-female ratio: 50/39), with a mean age of 64.08 ± 13.23 years (the age range: 26-88 years). Among them, early recurrence was observed in 57 (64%) patients, while late recurrence occurred in 32 (36%) after their initial symptomatic DVT episode. Late RDVT predominantly manifested in the contralateral lower extremity. Multivariate Cox regression analysis further identified proximal DVT, immobility, non-retrieved inferior vena cava filter (IVCF), and ≥50% stent extension into the inferior vena cava (IVC) as significant risk factors for late RDVT. Moreover, mortality among patients with late RDVT was low, with 2 (6.25%) dying during the follow-up period. Conclusions Late RDVT is relatively infrequent within the RDVT cohort and primarily manifests in the contralateral lower extremity. Furthermore, patients with late RDVT have a low mortality rate. Proximal DVT, immobility, non-retrieved IVCF, and ≥50% stent extension into the IVC are strongly correlated with the development of late RDVT.